Enhancing Cybercrime Response Capabilities through Integrated Digital Policing Systems - Rudy Cahya Kurniawan (Jurnal Scientia Indonesia, 2025)
This study examines the development of digital policing systems as a strategic response to the increasing complexity of cybercrime in Indonesia. As society becomes more dependent on digital platforms, cyber threats such as online fraud, identity theft, ransomware, and cyber harassment continue to escalate. This research aims to assess the effectiveness of integrated cybercrime response mechanisms that combine digital forensics, interagency collaboration, and AI-based threat detection. A mixed-methods design was employed, involving statistical analysis of national cybercrime reports from 2018–2023 and interviews with cyber investigators, IT specialists, and victims. Results indicate that the implementation of integrated digital policing systems reduced case-handling time by 31% and improved evidence retrieval accuracy by 27%. Interview findings highlight improved investigative coordination, although challenges persist related to technological disparities and public digital literacy. This study concludes that enhancing cybercrime response requires a comprehensive framework that merges technology, legal infrastructure, and cross-sector collaboration. The findings contribute to ongoing efforts in strengthening national cyber resilience.